Efficacy of Several Synthetic Insecticides against Mortality of the Fall Armyworm Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae) - Mursyidin, Abdul Halim; Pandya, Lalu Wahyu Ardis; Supeno, Bambang (CELEBES Agricultural, 2026)
Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae) is a major polyphagous corn pest that has caused significant corn yield losses in Indonesia. Synthetic insecticides are still the primary choice, but their effectiveness in the field against S. frugiperda larval mortality is determined by the active ingredient and concentration used. This study aimed to evaluate the efficacy of several synthetic insecticides with the active ingredients cypermethrin, abamectin, and a combination of emamectin benzoate + chlorfenapyr on the mortality and time-response of S. frugiperda larvae on corn plants through laboratory testing. The study used a completely randomized design (CRD) with six treatments and four replicates. Larval mortality was observed at 6, 12, 24, 36, and 72 hours after treatment (HAT) and analyzed using the Kruskal-Wallis test at a significance level of 5% (α = 0.05). The results showed that corrected mortality at 72 HAT ranged from 85–100% across synthetic insecticide treatments, caused mortality in S. frugiperda larvae with symptoms such as decreased feeding activity, paralysis, body color changes, and shriveled death. The combination of emamectin benzoate + chlorfenapyr at the highest consentration caused 100% mortality within 12 HAT, whereas cypermethrin reached complete mortality at 24 HAT. Abamectin exhibited a more gradual increase in mortality up to 72 HAT. Numerically, the combination treatment demonstrated a more rapid mortality response than the single active ingredient treatments. These results indicate that all tested synthetic insecticides were effective against third instar S. frugiperda larvae, although differences in the speed of mortality response were observed among treatments.